Art as a Tool of Cultural Diplomacy and the Part of Creative Industry: Case Study of South Korea (International relations and international law Journal, 2025)
In the context of rapidly changing global political and economic dynamics, the study of the interplay between culture, communication, and global transformations is becoming increasingly relevant. In recent years, particular attention has been paid to issues related to cultural diplomacy and soft power as tools of state influence on the international stage. This article explores approaches to analyzing cultural diplomacy through the lens of contemporary theoretical and methodological frameworks, including concepts of cultural identity, intercultural dialogue, and globalization challenges.The purpose of this study is to identify the specific features of cultural diplomacy in the context of transforming international relations and to assess its influence on shaping the image of a state in global public opinion. The article analyzes the mechanisms of cultural communication, the role of cultural institutions, and the interaction between official structures and civil society in promoting national cultural agendas.The methodological foundation of this research is based on interdisciplinary approaches, including comparative analysis, discourse analysis, and case study methods. The study draws on both domestic and international sources, examining the experiences of various countries in the field of cultural diplomacy, including the activities of institutions such as the British Council, Goethe-Institut, and Institut Français, among others.The practical significance of the study lies in the fact that the conclusions and recommendations developed by the authors can be used in the formulation of national cultural policy strategies, as well as in educational and analytical contexts. Furthermore, the research contributes to a deeper understanding of culture as a resource for sustainable development and intercultural dialogue.Thus, the presented article contributes to the academic discourse on cultural diplomacy, highlighting its potential as an effective tool of international communication in the era of global transformations.Keywords: South Korea, museum studies, cultural diplomacy, creative industries, soft power.